2019
DOI: 10.3390/s19061283
|View full text |Cite
|
Sign up to set email alerts
|

Robust Identification of Strain Waves due to Low-Velocity Impact with Different Impactor Stiffness

Abstract: Low-velocity impacts represent a major concern for aeronautical structures, sometimes producing barely detectable damage that could severely hamper the aircraft safety, even with regards to metallic structures. For this reason, the development of an automated impact monitoring system is desired. From a passive monitoring perspective, any impact generates a strain wave that can be acquired using sensor networks; signal processing techniques allow for extracting features useful for impact identification, possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Impacts generate lamb waves that propagate outwards from the impact location as the source [8,9,10]. These waves have been used to identify the location of impacts using multiple methods available [8,9,10,11,12,13,14,15,16,17]. Methods that are based on the physical behaviour of wave propagation in the observed structure may require complex modelling/solving [8,15,18] or may not be suited to complex structures (cut outs, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impacts generate lamb waves that propagate outwards from the impact location as the source [8,9,10]. These waves have been used to identify the location of impacts using multiple methods available [8,9,10,11,12,13,14,15,16,17]. Methods that are based on the physical behaviour of wave propagation in the observed structure may require complex modelling/solving [8,15,18] or may not be suited to complex structures (cut outs, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, besides the parameters assessed in the study [23], variation of impacts can also come from differences in impactor stiffness caused by different impactors (debris, bird strike, tools, etc.) [10]. Out of the few studies that have investigated the effect of impactor stiffness on the generated lamb waves, it was found that lower impactor stiffness generates significantly lower frequency lab waves [10,15,18,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation